2014
DOI: 10.15603/2177-7284/regs.v5n2p1014-1032
|View full text |Cite
|
Sign up to set email alerts
|

Clusters de Pequenas e Médias Empresas e Desenvolvimento Regional

Abstract: No Brasil, as ações dirigidas ao desenvolvimento de clusters tiveram abordagem oficial como política pública em 2004, com a criação do GTP APLs (Grupo de Trabalho Permanente para APLs), coordenação pelo MDIC (Ministério do Desenvolvimento, Indústria e Comércio Exterior). Para o GTP, um APL é caracterizado a partir da concentração de um número significativo de empresas em um dado território, enfatizando-se as melhores práticas para induzir a ganhos técnicos, produtivos e de mercado, e onde a cooperação entre os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 1 publication
1
4
0
3
Order By: Relevance
“…In general, corroborating Dias (2011), Jacometti, Castro, Gonçalves et al (2016), and Macedo, Araújo and Campos (2014), this study found that government investment in LPAs generates positive impacts on development when the analysis uses the Propensity Score Matching technique.…”
Section: Final Considerationssupporting
confidence: 83%
See 4 more Smart Citations
“…In general, corroborating Dias (2011), Jacometti, Castro, Gonçalves et al (2016), and Macedo, Araújo and Campos (2014), this study found that government investment in LPAs generates positive impacts on development when the analysis uses the Propensity Score Matching technique.…”
Section: Final Considerationssupporting
confidence: 83%
“…In this case, unlike that observed with the Propensity Score Matching, only in the period 2005-2013 was a positive and significant impact on GDP identified. As highlighted, it was assumed that the LPAs are environments favorable for development (LASTRES and CASSIOLATO, 2003) and that making investments enhances their capacity and promotes development (DIAS, 2011;JACOMETTI, CASTRO, GONÇALVES et al, 2016;MACEDO, ARAÚJO and CAMPOS, 2014). Despite the different techniques, the results may be used for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations